2007
DOI: 10.1126/science.1136099
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Dominance of Teams in Production of Knowledge

Abstract: The Increasing Dominance of Teams in Production www.sciencemag.org (this information is current as of November 24, 2009 ):The following resources related to this article are available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

79
1,889
7
50

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,716 publications
(2,118 citation statements)
references
References 13 publications
79
1,889
7
50
Order By: Relevance
“…Background S everal studies [1][2][3][4] have documented that, since the mid-1950s, the natural, behavioral, and social sciences have made a pronounced shift from individually oriented research toward team-based scientific initiatives. This trend toward greater teamwork in science is paralleled by a growing emphasis on crossdisciplinary approaches to research and training.…”
Section: Resultsmentioning
confidence: 99%
“…Background S everal studies [1][2][3][4] have documented that, since the mid-1950s, the natural, behavioral, and social sciences have made a pronounced shift from individually oriented research toward team-based scientific initiatives. This trend toward greater teamwork in science is paralleled by a growing emphasis on crossdisciplinary approaches to research and training.…”
Section: Resultsmentioning
confidence: 99%
“…Wuchty et al (2007) reported that coauthored social science articles increased from 17.5% to 51.5% between 1955 and 2000, an increase that was observed in all 54 subfields (see also Zuckerman & Merton, 1972). In addition, the mean number of authors per article nearly doubled, increasing from 1.4 to 2.5.…”
Section: Collaboration and Coauthorshipmentioning
confidence: 98%
“…In the main, it describes a shift from an individual to a teamwork model of science over the past century, that is, from small science to big science, especially after World War II (Price, 1963). Wuchty, Jones, and Uzzi (2007), for instance, reported that the percentage of coauthored articles in science and engineering increased from 53% to 82% between 1955 and 2000, an increase that occurred in 170 of 171 subfields (99.4%). In addition, the mean number of authors per article nearly doubled, increasing from 1.9 to 3.5.…”
Section: Collaboration and Coauthorshipmentioning
confidence: 99%
“…Intriguing work on publication co-authorship has suggested that there have been fundamental changes in the size and nature of collaboration (Jones, 2009; Wuchty et al, 2007). Linked UMETRICS data enable us to look at project level collaborations.…”
Section: Using the Datamentioning
confidence: 99%